Liquid Metal Leaching for Rare Earth Magnet Recycling - Emmanuel Opoku; Chinenye Chinwego; Adam Powell; Brajendra Mishra (Metals)
This study investigates the optimization of liquid metal leaching for recycling rare earth elements (REEs) from NdFeB magnets, a critical step in addressing the increasing demand for these materials in various high-tech applications. We explored the effects of leaching time, stirring, and magnet demagnetization on the yield of the leaching process using molten magnesium. Conducted at 900 °C, our experiments assessed the leaching process over periods of 2, 3.5, and 5 h, with and without the application of stirring. Our findings show that longer leaching times considerably increase neodymium (Nd) and praseodymium (Pr) leaching yield, with a notable peak in efficiency found at 5 h. Stirring improved the uniformity of REEs significantly and resulted in up to 80% yield. Furthermore, our data show that pre-leaching magnet demagnetization improves leaching specificity, significantly reducing the presence of non-target metals like nickel and copper. These insights offer a pathway to more cost-effective recycling of REEs from magnet scrap, which is essential for environmentally conscious management of resources amid the escalating global demand for REEs.